Ķīniešu mūzikas terapijas idejas: tradīcija un tās interpretācija 21. gadsimtā - Özcoşkun, Dilge Bengü (Latvijas Universitāte, 2020)
Music therapy is one of the oldest methods known in China and other countries for healing patients. Many civilizations emphasized the importance of music and realized that it could be effective in treatment and applied it. Here, music has a nourishing emotion by influencing the depths of the soul with harmony and rhythm. When it comes to Chinese music therapy, it is often remembered that there are scenes where the patient is only a listener and heals by listening to Chinese music. This study also plays a role in eliminating this perception. Because the active music therapy approaches that the patient participates in the music production process, where musical dialogue comes to the fore, and the therapist observes the patient while producing music are discussed in this study. The impact of music on human life, its relationship with mental health and the necessity of music education are very important today. Music today is used as supportive therapy for the healing of patients in contemporary societies. Therefore, various approach techniques are used in China. Music therapy, which is slowly becoming widespread in the world, is a work I have written to guide the people who are learning this field, to provide a better understanding of the discipline of music therapy, to arouse curiosity, to solve problems and to fill this gap. This research has been carried out with the aim of believing that this field where knowledge, love, creativity, energy and labor are combined and will develop and be an important resource. Since music and approaches to music constitute the common language between people, I have explained the studies applied on this language, and I have dealt with some problems that have arisen and solved them. After a long period of research for this study, I decided to start with the latest emerging medical branch of China, music therapy. What I am aiming at with this beginning is to explain music therapy on the one hand, and to help music therapists find something of themselves in this research, on the other hand, to help music therapy people to perceive their own feelings. As a musician, I thought of myself during a therapy session. The most important goal I find in the research process is to make music therapy professionals feel that I am not only a researcher or a student, but I am also a musicist, a knowledge of Asian culture and a humanist. In this study, you will find that I deal with both theoretical and artistic developments. While this study aims to introduce people to music therapy, it also reveals the efforts to convey the issues in this field in the most analytical ways. It also fills an important gap, especially given the minority of Chinese music therapy resources. I discussed the topics in the study from a few perspectives and explained their approaches, building system and suggestions. I wanted to address the roof that provided the formation of my current musician identity, and the existence of a b
Ideas of Chinese Music Therapy: Tradition vs. its Interpretation in the 21st Century
Keywords: Āzijas studijas; Music Therapy; Chinese Music Therapy; Music; Therapy; Chinese